Evaluation of Old Oyo National Park efficiency using DEA approach - Daniel Jacob; Samuel Onadeko; Imaobong Nelson; Abdul Shotuyo (Economic and Environmental Studies (E&ES), 2018)
Measuring the efficiency of a national park is difficult due to, among other factors, the heterogeneity of resources supplied (e.g., budget, staffs) and outcomes expected (e.g., income, visitors' flow). While this is an issue in protected area management, it has been approached successfully in other fields by using data envelopment analysis (DEA). DEA has a number of advantages over other techniques as it simultaneously uses multiple heterogeneous inputs and outputs to determine which projects are performing most efficiently, referred to as being at the efficiency frontier, when compared to others in the data set. This study therefore uses DEA for the evaluation of management efficiency in Old Oyo National Park for the period of 2001-2015. The results showed that the park was efficient for 11 and 13 years, respectively, in terms of its overall technical and pure technical efficiency with a mean scale efficiency of 97%. Also, the park operated at 80% of its productive scale size. These results, and the use of DEA, highlight both the success of using this technique in helping determine protected area efficiency and those factors to consider while allocating resources for new projects at the park.
Keywords: Q56; Q57; Q58; 330; national park; efficiency; resource allocation; protected area management